Study of Halal Tourism Village Based on Creative Economy in Canting Village, Landungsari, Pekalongan City - Adinugraha, Hendri Hermawan; Ma’ruf, Hasan (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
The objectives of this study are to describe how big the potential of the Kampung Canting Landungsari in Pekalongan City is as a representation of a creative economy-based halal tourism village, to explain economic activities in empowering the Kampung Canting Landungsari community as a village that has the potential to become a halal tourism village based on a creative economy, analyzed the concept of a creative economy- based hala tourism village in Kampung Canting Landungsari, Pekalongan City. This research is a type of qualitative research. The data collection method in this study used interviews and observation with a total of 6 informants. The sampling technique was purposive sampling. This research uses a data reduction analysis method. The results showed that the Kampung Canting Landungsari, Pekalongan City has great potential for representing a halal tourism village based on a creative economy. Apart from operating as a tourism center, Kampung Canting Landungsari is an area that is thick with religious culture. Then several main elements must be met to analyze the concept of a Halal Tourism Village based on a creative economy. Several criteria have been met by Kampung Canting Landungsari, but there are still criteria that need to be improved again to become a Halal Tourism Village.